Needlestick and sharps injuries at a German university hospital: epidemiology, causes and preventive potential – a descriptive analysis - Manmeet Kaur; Sonja Mohr; Gabriele Andersen; Olaf Kuhnigk (International Journal of Occupational Medicine and Environmental Health, 2022)
Objectives To analyze the number, epidemiology and circumstances of needlestick and sharps injuries (NSSI) and exposures to body fluids and to identify further preventive measures to improve the occupational safety of health care workers (HCW).